Racial/Ethnic Disparities in Health-Related Quality of Life among Participants with Self-Reported Diabetes from NHANES 2001-2010. (July 2014) - Zhang, Lu; Ferguson, T. Freeman; Simonsen, Neal; Chen, Liwei; Tseng, Tung-Sung
Purpose: The purpose of this study is to investigate the racial/ethnic disparities in health-related quality of life (HRQOL) among adults with self-reported diabetes and identify the different risk factors related to HRQOL for specific racial/ethnic groups in the United States. Methods: National Health and Nutrition Examination Survey (NHANES) 2001-2010 participants (ages 20 years and older) who were self-identified as non-Hispanic white, non-Hispanic black, or Hispanic and with self-reported diabetes were included in the analysis (n = 2594). The Centers for Disease Control and Prevention's HRQOL-4 was used to assess factors associated with HRQOL through multivariate logistic regression models with survey weighting. Stepwise model selection was applied to select the most significant factors for HRQOL in each racial/ethnic group. Results: Hispanic participants were less likely to report 14 or more mentally unhealthy days and activity-limited days compared to non-Hispanic white counterparts, adjusting for age, sex, education, marital status, family poverty–income ratio (PIR), body mass index, smoking status, insurance coverage, and diabetes duration. Current smoking status and obesity were significantly associated with worse HRQOL among whites and blacks. Marital status predicted better HRQOL only among Hispanics. Having insurance coverage predicted better HRQOL among both blacks and Hispanics. Increased family PIR had a favorable association with the 4 HRQOL domains consistently among all races/ethnicities. Conclusion: Minimal racial/ethnic disparities in HRQOL were observed among US adults with self-reported diabetes. Support is offered for more individualized health care and communication with patients to target care and interventions that improve health and quality-of-life indicators.